Small Firm Growth in Lima, Peru: A Multiple Case Study - Espinoza Pazos, Fernando Clemente (Pontificia Universidad Católica del Perú, 2021)
The main goal of this article is to identify factors associated with the growth of micro and small enterprises (MSEs) in Lima, Peru from the perception of the entrepreneurs themselves based on a qualitative multiple case study under a holistic approach. Therefore, the study analyzes 18 MSE cases in Lima divided intotwo groups: companies experiencing continuous growth and companies that do not experience continuous growth. The results showed that one of the factors that seem to be characteristic of the first group is the constant motivation to take advantage of business opportunities. On the contrary, one of the factors present in the second group is the motivation to meet temporary needs. This article contributes to the understanding of MSEs in Lima and expands the existing knowledge on the factors associated with growth and market consolidation by studying the entrepreneurs’ perceptions.
Keywords: Firm growth; Small enterprise; MSE; microenterprise; Peru; https://purl.org/pe-repo/ocde/ford#5.02.04